A Debreceni Egyetem centenáriumi előkészületei - szerkesztőbizottsága, A folyóirat (Gerundium, 2011)
Centenary Preparations at the University of Debrecen. The editors of the journal offer status reports on the preparations for the centenary celebrations of the University of Debrecen in 2010. Special attention is devoted to those publications which thematize the history of the university (as well as the history of its predecessor institutions) and of the faculties, of which pre-eminent position is occupied by the commemorative centenary volume offering a comprehensive history of the university in answer to the expectations and requirements of the 21st century. Brief surveys are provided of preparatory projects such as the ones aimed at establishing a Museum of the University, the processes of conducting interviews pertaining to the history of the university, as well as the emerging programs of the centenary year.